2022
DOI: 10.1038/s41598-022-06879-0
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of ultrasound-guided attenuation parameter (UGAP) to the noninvasive evaluation of hepatic steatosis

Abstract: The aim of this study was to identify the applicability of an ultrasound-guided attenuation parameter (UGAP) for the noninvasive assessment of hepatic steatosis in clinical practice and to compare its correlation with B-mode ultrasound (US). From May to July 2021, 63 subjects with different body mass index (BMI) grades were included in the prospective study. All of them performed UGAP measurements, under different breathing manipulations, positions, diet statuses, and operators. After that, the UGAP values wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
4
3
0
Order By: Relevance
“…In our study, we found that TAI and TSI measurements demonstrate strong correlation with visual hepatic steatosis grades and there was a significant difference in TAI and TSI measurements across different visual hepatic steatosis grades. These findings were consistent with previous studies reported that various ultrasound‐based techniques used to quantify liver fat content are correlated with visual hepatosteatosis grades and have significant differences according to visual hepatosteatosis grades 17–19 . Therefore, our study supports the clinical applicability of QUS techniques for the diagnosis of hepatosteatosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, we found that TAI and TSI measurements demonstrate strong correlation with visual hepatic steatosis grades and there was a significant difference in TAI and TSI measurements across different visual hepatic steatosis grades. These findings were consistent with previous studies reported that various ultrasound‐based techniques used to quantify liver fat content are correlated with visual hepatosteatosis grades and have significant differences according to visual hepatosteatosis grades 17–19 . Therefore, our study supports the clinical applicability of QUS techniques for the diagnosis of hepatosteatosis.…”
Section: Discussionsupporting
confidence: 93%
“…Strauss et al 12 reported that visual assessment of hepatosteatosis on ultrasonography has substantial observer variability. However, recent studies that were designed to assess reproducibility of various QUS techniques reported high agreement levels for visual hepatic steatosis grades and our results were in line with these studies 17,18 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, further studies comparing many repetition protocols using several ultrasound attenuation platforms are needed. Finally, UGAP measurements were made by only one radiologist, although previous studies have demonstrated high intraobserver and interobserver reproducibility [ 35 , 36 ]. Additionally, the second set of six measurements might have been influenced by the first set of six measurements because all measurements were continuously performed by the same observer; however, this study focused on the preceding six measurements, which were not affected by the following six measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the latter point, minor steatosis or small changes over time in hepatic fat deposits would preferably be studied with the Controlled Attenuation Parameter (CAP) algorithm implemented in the transient elastography (FibroScan) system, and the Ultrasound-Guided Attenuation Parameter (UGAP). These imaging techniques are an accurate diagnostic tool for the point-of-care investigation of MAFLD [ 46 ], but they are not commonly available in internal medicine clinics.…”
Section: Discussionmentioning
confidence: 99%